Displaced thermal state QKD simulation data set: Mutual information changes with loss - Walton, Adam; Ghesquiere, Anne; Jennings, David; Varcoe, Benjamin (University of Leeds, 2021)
Simulation results showing the effects of loss on mutual information measurements in a thermal QKD protocol.
Keywords: FOS: Physical sciences